Rasa Theory Applied to William Shakespeare’s Twelfth Night - Budhathoki, Mahendra Kumar (Literary Studies, 2020)
The primary purpose of the paper is to study Shakespeare’s plays Twelfth Night (Western literature) through rasa theory i.e. an Eastern literary theory. Rasa etymologically refers to liquid, flavour, taste, elixir, essence, pleasure, beauty. Literary meaning of rasa, as Bharata defines, is that which is relished or enjoyed. He describes rasa as the delight that the readers experience the generalized emotions presented in the dramatic art. Rasa is a study of universal human emotions. “Rasa is the […] study of emotions which deals with the delight, one takes in literature” (Poonam 5). The ultimate goal of rasa theory is to act as a catalyst to enhance aesthetic delight in literature. Rasa as the soul makes the literature alive. “The aim of performance [is] to evoke [sentiment] in the mind of audience” (Keith 314). Dramatic works appeal to human heart. “Rasa theory embraces humanism as a whole. It does not leave out any of the emotions, which could produce rasa. Rasa theory therefore is an all-pervasive humanistic theory” (Fernando 35). Readers appreciate and relish literature that provides aesthetic enjoyment.